PRACTICAL TRAINING OF STUDENTS AT POLISH UNIVERSITIES USING WSG UNIVERSITY IN BYDGOSZCZ AS AN EXAMPLE - Sobczak-Michałowska, Marzena (The Modern Higher Education Review, 2021)
Reflections about strategic development of vocational education require not only a reliable diagnosis of selected socioeconomic conditions, but all the above forecasts based on this diagnosis. Modern education is a symbiosis of relations with its socioeconomic environment. In recent years these relations have been generally one-sided, the so called environment has tried to influence the directions and programs of vocational education. As a result, educational institutions have been under pressure from the labor market. Nowadays, there is the two-side connection in which institutions of vocational education begin to affect - through their graduates – the labor market.